Vascular endothelial growth factor correlation with clinicopathological parameters in ovarian cancer - Egiz, Mahy; Masoud, Alaa; Ellakwa, Hamed; Adel Elsayed, Mohamed (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Epithelial ovarian cancer (EOC) is one of the most lethal gynaecologic malignancies with an increasing incidence worldwide; there is an increasing need for the identification of novel prognostic biomarkers in EOC patients. Given the key role of angiogenesis and growth factors in the biology of tumorigenesis, vascular endothelial growth factor (VEGF) is considered a milestone in the process of ovarian cancer progression and invasiveness. Authors aimed in the present study to evaluate the relevance of serum level of VEGF with clinicopathological parameters in patients with EOC. VEGF is reported to be correlated with variable parameters in EOC patients including International Federation of Gynecology and Obstetrics (FIGO) classification, lymph nodal involvement and ascites formation. In the following review, authors discussed these correlations and distinguished the possible future role of VEGF as a promising prognostic biomarker for EOC patients.